Effects of oily fish intake on cognitive and socioemotional function in healthy 8–9-year-old children: the FiSK Junior randomized trial. Issue 1 (12th June 2020) - Teisen, Marie N; Vuholm, Stine; Niclasen, Janni; Aristizabal-Henao, Juan J; Stark, Ken D; Geertsen, Svend S; Damsgaard, Camilla T; Lauritzen, Lotte
ABSTRACT: Background: Long-chain n–3 PUFAs (n–3 LCPUFAs) accrete in the brain during childhood and affect brain development. Randomized trials in children show inconsistent effects of n–3 LCPUFAs on cognitive and socioemotional function, and few have investigated effects of fish per se . Objectives: We aimed to investigate the effects of oily fish consumption on overall and domain-specific cognitive and socioemotional scores and explore sex differences. Methods: Healthy 8–9-y-old children ( n = 199) were randomly allocated to receive ∼300 g/wk oily fish or poultry (control) for 12 ± 2 wk. At baseline and endpoint, we assessed attention, processing speed, executive functions, memory, emotions, and behavior with a large battery of tests and questionnaires and analyzed erythrocyte fatty acid composition. Results: One hundred and ninety-seven (99%) children completed the trial. Children in the fish group consumed 375 (25th–75th percentile: 325–426) g/wk oily fish resulting in 2.3 (95% CI: 1.9, 2.6) fatty acid percentage points higher erythrocyte n–3 LCPUFA than in the poultry group. The overall cognitive performance score tended to improve by 0.17 (95% CI: −0.01, 0.35) points in children who received fish compared with poultry, supported by n–3 LCPUFA dose dependency. This was driven mainly by fewer errors [−1.9 (95% CI: −3.4, −0.3)] in an attention task and improved cognitive flexibility measured as faster reaction time [−51 ms (95% CI: −94, −7 ms)] in a complex relative to a simple task ("mixing cost"). The fish intervention furthermore reduced parent-rated Strength and Difficulties Questionnaire total difficulties by −0.89 (95% CI: −1.60, −0.18) points mainly due to a −0.63 (95% CI: −1.11, −0.16) points reduction in internalizing problems that was reflected in tendency to a decrease in the overall socioemotional problems score of −0.13 (95% CI: −0.26, 0.01) points. The overall effects were similar in boys and girls. Conclusions: Oily fish dose-dependently improved cognitive function, especially attention and cognitive flexibility, and reduced socioemotional problems. The results support the importance of n–3 LCPUFAs for optimal brain function and fish intake recommendations in children. The trial was registered at www.clinicaltrials.gov as NCT02809508.